Offshoring business process services and governance control mechanisms: An examination of service providers from India - Jayaraman, V.; Narayanan, S.; Luo, Yadong; Swaminathan, J. (2013)
As emerging markets increasingly rely on service businesses through offshore outsourcing, we examine the role of governance control mechanisms in improving performance among business process outsourcing (BPO) service providers in India. Using data collected from 205 emerging market-based BPO service providers in India, we examine the antecedents and consequences of establishing governance control mechanisms in BPO service providers. Specifically, we examine how structural (use of contracts with the client), administrative (effective allocation and demarcation of responsibilities within the firm), and relational (collaboration and information sharing with the client) mechanisms drive the performance of a BPO service provider operating in an emerging market. We also examine how key task-related (task connectivity and task security) and client-related (end customer orientation and global control) antecedents influence the use of different governance control approaches in this environment. Our analysis finds that both task connectivity and task security significantly impact use of structural and administrative mechanisms, whereas end customer orientation is significantly associated with the strength of the relational mechanisms governing the emerging market-based BPO service provider and its client. Further global control significantly influences the strength of the structural mechanisms between the client and the BPO service provider. Finally, the three mechanisms have a complementary influence in driving the BPO service provider's performance.